Analysis of CIC-associated CpG island methylation in oligoastrocytoma - Sahm, Felix; Lass, U.; Herold-Mende, Christel; Deimling, Andreas von; Hartmann, Christian; Müller, Wolf C. (Neuropathology & applied neurobiology, 2013)
Aims Combined deletion of the whole chromosomal arms 1p and 19q is a frequent event in oligodendroglial tumours. Recent identification of recurrent mutations in CIC on 19q and FUBP1 on 1p and their mutational patterns suggest a loss of function of the respective proteins. Surprisingly, oligoastrocytomas harbouring identical genetic characteristics regarding 1p/19q codeletion and frequent IDH1/2 mutations have been shown to carry CIC mutations in a significantly lower number of cases. The present study investigates whether epigenetic modification may result in silencing of CIC. Methods As IDH1/2 mutation-mediated DNA hypermethylation is a prominent feature of these tumours, we analysed a set of CIC wild-type oligoastrocytomas and other diffuse gliomas with regard to 1p/19q status for presence of CIC-associated CpG island methylation by methylation-specific PCR. Results Both methylation-specific PCR and subsequent bisulphite-sequencing of selected cases revealed an unmethylated status in all samples. Conclusion Despite the hypermethylator phenotype in IDH1/2 mutant tumours and recent detection of gene silencing particularly on retained alleles in oligodendroglial tumours, hypermethylation of CIC-associated CpG islands does not provide an alternative mechanism of functional CIC protein abrogation.
Gesehen am 25.01.2022